Analisis Kelayakan Finansial dan Sensitivitas Usaha Keripik Okra pada UKM XYZ - Rafhani Ziana; Rahayu Relawati (LPPM Universitas Malikussaleh - Indonesia, 2026)
Horticulture-based food processing businesses have high value-added potential, but require a thorough financial evaluation to ensure business sustainability. This study aims to analyze the financial feasibility and sensitivity of the okra chips business in XYZ SMEs during the period 2021–2025 with a quantitative descriptive approach using primary and secondary data. The financial feasibility analysis was carried out using the Net Present Value (NPV), Gross Benefit Cost Ratio (Gross B/C), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP) indicators, and was complemented by sensitivity analysis to changes in investment, operational costs, and benefits. The results of the study show that the okra chips business is feasible to develop with a positive NPV value of IDR 990,112,958, Gross B/C of 1,337, Net B/C of 3,870, IRR of 88.48% which is greater than the Discount Rate, and a Payback Period of 0.9997 years, while sensitivity analysis shows that businesses are relatively insensitive to the increase in initial investment but sensitive to changes in operational costs and receipts.